International Journal of Geo-Engineering - Bang, Sangchul; Finno, Richard J.; Lee, Jong-Sub
The goal of this interdisciplinary journal is to provide a forum to discuss the knowledge and experience of geo-engineering from fundamentals to cutting edge technologies.